The Role of Teacher and English Textbook in Boosting the 7th Graders’ Critical Thinking Skills: A Case Study - Marisa Linia; Sri Rachmajanti; Siti Muniroh (STAI Hubbulwathan Duri, 2025)
This study investigates a junior high school teacher’s understanding and application of critical thinking and the English for Nusantara textbook in teaching seventh-grade students under Indonesia's liberated curriculum, which emphasizes critical thinking as a 21st-century skill. Conducted as a case study in a junior high school in Madura, Indonesia, the research involved one English language teacher. Data were collected through interviews, textbook analyses, and classroom observations. The teacher demonstrated adequate critical thinking knowledge, gained through Professional Instructor Education Training, and assessed students' skills using Bloom’s Taxonomy. The teacher actively facilitated argumentation and critical thinking in class activities. While the English for Nusantara textbook served as a reference for class topics, an analysis of Chapters 1–3 revealed a lack of critical thinking exercises. To address this, the teacher employed various strategies, such as critical questioning, brainstorming, and hands-on activities, to develop students' critical thinking. Visual aids were also used to enhance engagement and understanding. Findings indicate that the teacher’s approach promoted deep and reflective thinking among students. Despite the textbook’s shortcomings, integrating diverse methods and resources effectively developed students' ability to acquire, evaluate, and apply information to solve problems. The study underscores the importance of critical thinking in education and highlights the need for improved textbook content to support this goal.